Parametric Coding of Binaural Audio - Bjärnklint, Viktor (My University, 2020)
Binaural cue coding, BCC, presumes that the signals in the two channels differ primarily with respect to time, level, and coherence. The method then assumes that both channels can be synthesised by imposing the according time, level, and coherence differences onto a single-channel signal. BCC can generally be split into two major parts: encoding and decoding. Encoding represents the analysis of the signal and investigates the signal’s inter-channel time and level differences as well as the inter-channel coherence. The signal’s channels are then summed, the signal is downmixed. The decoding process upmixes the singlechannel signal to its original number of channels and restores the inter-channel time and level differences and uses the inter-channel coherence to mimic the inter-channel coherence of the original audio signal. Binaural signals, signals consisting of two channels each filtered with head related transfer functions, HRTFs, are sensitive to compression algorithms since they depend on a highly delicate time and level differences between the two channels. Thus, the thesis is focused on the low-complexity implementation of the BCC scheme presented by Faller in his Phd thesis Parametric Coding of Spatial Audio and how well this scheme can synthesise the spatial cues present in binaural signals. The result and analysis is divided into two parts: a simple analysis used to investigate the general performance of the implemented algorithm and an informal listening test evaluating how well the program handles the synthesis of the binaural signals. The synthesised audio exhibits a varied intensity of artefacts if the ICTD synthesis is incorporated in the BCC process. If the ICTD synthesis is left out of the BCC process, almost no artefacts can be perceived. However, this reduces the lateralization of the sounds/sound sources present in the audio. The conclusion that follow is thus that the implementation illustrates the potential the method has for transferring high complexity audio, such as binaural signals, at low bitrates.
Keywords: BCC, binaural, ICC, ICTD, ICLD, audio, sound